Physical and Biochemical Characterization of Sweet Corn Ears of Four Varieties Grown in Senegal - Ndiaye, Nafissatou Diop; Cisse, Mady; Mbacke, Fatou Diop; Diop, Abou; Ndiaye, Saliou; Thompson, Thomas (European Scientific Journal, ESJ, 2017)
Sweet corn is an underutilized crop for human consumption in Senegal. In this study, physical and biochemical characterization were performed on four sweet corn ear varieties grown at three different fertilization rate of 15N-15-P-15K. Treatment F1 was 40 tons/Ha horse-dung + 200 kg/Ha of 15N-15P-15K, treatment F2 was 30 tons/Ha horse-dung + 150 kg/Ha of 15N-15P-15K) and treatment F3 was 50 tons/Ha horse-dung + 250 kg/Ha of 15N-15P-15K. Results showed that Yosemite cultivar gave the highest number of kernels/ear (672.3), followed respectively by Legacy (642), Excellis Garrison (585.6) and Infinity (573). Furthermore, treatments using fertilizer 3 (F3: 50 tons/Ha horse-dung + 250 kg/Ha of 15N-15P-15K) led to the highest number of kernels/ear in all cultivars used. Interestingly, Legacy cultivar gave more reducing sugars (5.1 ± 0.8 g.100g -1 ) with treatment F1; treatment F3 provided less reducing sugars (2.1 ± 0.6 g.100g -1 ) and more starch (14.4 ± 0.5 g.100g -1 ). Overall, physical and biochemical characteristics were influenced to at least some extent by fertilization treatments related to the cultivar used. Yosemite and Legacy cultivars would be more suitable for canned sweet corn production in the conditions studied. Sangalkam seems to be more suitable for sweet corn production.